The Role of Glyoxal, an Advanced Glycation Product, in Diabetic and Non-diabetic Patients with COVID-19 - Işıksaçan, Nilgün; Şahingöz Erdal, Gülçin; Teksöz, Duygu; Kasapoğlu, Pınar; Yaman, Mustafa; Uğur, Halime; Kart Yaşar, Kadriye; Yaman, Mustafa (Galenos Yayınevi, 2024)
Objective: The aim of this study was to investigate the effect on coronavirus disease-2019 (COVID-19) of glyoxal (GO), which is a precursor of advanced glycation end-products, in diabetic and nondiabetic patients, treated in hospital for COVID-19 who were of similar age and disease severity with similar comorbidities. Methods: The study included 57 patients. Measurement of GO was made with the high-performance liquid chromatography method. Results: The GO values were found to be higher in the diabetic group than in the non-diabetic group (p=0.001, p<0.01). The length of stay in hospital was longer in the diabetic group (p=0.017, p<0.05). The white blood cell, neutrophil, neutrophil/lymphocyte ratio, procalcitonin, and ferritin values were determined to be higher in the diabetic group than in the non-diabetic group (p=0.006; p=0.005, p=0.017, p=0.011, p=0.030). Although the mortality and intensive care unit admission rates were similar in the diabetic and non-diabetic patients of similar age with similar comorbidities and COVID-19 severity, the total length of stay in hospital was determined to be longer in the diabetic patients.Together with other inflammation markers, GO, was determined to be higher in the diabetic group. Conclusion: The results of this study showed that elevated GO could be associated with a prolonged recovery time in COVID-19.

Amaç: Bu çalışmanın amacı, ileri glikasyon son ürünlerinin öncülü olan glioksalin (GO), koronavirüs hastalığı-2019 (COVID-19) nedeniyle hastanede tedavi gören benzer yaş ve benzer komorbiditeli hastalık şiddetine sahip diyabeti ve diyabeti olmayan hastalardaki etkisini araştırmaktır. Yöntemler: Çalışmaya 57 hasta dahil edildi. GO ölçümü yüksek performanslı sıvı kromatografi yöntemiyle yapıldı. Bulgular: Glioksal değerleri diyabetik grupta diyabetik olmayan gruba göre daha yüksek bulundu (p=0,001, p<0,01). Hastanede kalış süresi diyabetik grupta daha uzundu (p=0,017, p<0,05). Beyaz kan hücresi, nötrofil, nötrofil/lenfosit oranı, prokalsitonin ve ferritin değerlerinin diyabetik grupta diyabetik olmayan gruba göre daha yüksek olduğu belirlendi (p=0,006; p=0,005, p=0,017, p=0,011, p=0,030). Benzer yaştaki, komorbiditeleri ve COVID-19 şiddeti benzer olan diyabetik ve diyabetik olmayan hastalarda mortalite ve yoğun bakıma yatış oranları benzer olmasına rağmen, diyabetik hastaların hastanede toplam kalış süresinin daha uzun olduğu belirlendi. Diğer enflamasyon belirteçleriyle birlikte GO’nun diyabetik grupta daha yüksek olduğu belirlendi.Sonuç: Bu çalışmanın sonuçları, yüksek GO’nun COVID-19’da uzun süreli iyileşme süresiyle ilişkili olabileceğini gösterdi. Anahtar Sözcükler: İleri glikasyon son ürünleri, COVID-19, diyabet, glioksal, hastanede kalış süresi
COVID-19 Geçiren Diyabetli ve Diyabetli Olmayan Hastalarda İleri Glikasyon Ürünü Olan Glioksalin Rolü
Keywords: Advanced glycation end-products; COVID-19; Diabetes; Glyoxal; Length of stay in hospital; İleri glikasyon son ürünleri; COVID-19; Diyabet; Glioksal; Hastanede kalış süresi